Pengaruh Kualitas Layanan dan Penanganan Terhadap Keluhan Pelanggan PT Kawasan Berikat Nusantara (Persero) - Suwito, Jajang; Zuraidah, Eva (TIN: Terapan Informatika Nusantara, 2021)
PT.Kawasan Bonded Nusantara (Persero) is a company that manages an industrial area with the status of a bonded zone (Export Processing Zone). The problems that exist in the system company are still carried out slowly in handling customer complaint services directly, procedures that are not optimal to provide information to customers due to lack of knowledge of steps or procedures exist, and still have to use correspondence, and there is no clear solution to solve the problem. the solution and all complaints are only accommodated by making a letter, after the letter is made to be signed by the leadership it takes a long time and is inefficient, if needed by the staff in each department that requires it, how to deal with complaints from customers will greatly slow down the process of handling customer complaints , so customers are upset. From the results of the research above, the researcher concludes that the value of the perception gap and the value of the expectation gap from Tangible: the reality is worth 3.75, the expected value is 4.32 and the gap is -0.57. Responsiveness: reality value: 3.85, expectation value 4.37, gap value -0.51, Assurance reality value 3.61, expectation value 4.45 and gap value -0.85. Reliability: the actual value is 3.87 while the expected value is 4.44 the gap value is - 0.57. Empathy, the reality value is 4.05, the expected value is 4.44, the gap value is -0.39. From these results, for PT Kawasan Berikat Nusantara (Persero) it can also be seen from the 5 dimensions that servqual has a satisfaction value of 3.828, and an expectation value of 4.4.2 so that there is -0.575 This gap occurs due to the non-fulfillment of the influence of service quality expectations for customers. by employees of PT Kawasan Berikat Nusanatara (Persero) which must be considered is that all dimensions have negative gap values. Reliability is the first rank with a Gap value of -0.85